Changes in Knowledge About Mothers Stunting Before and After Watching the Video on Mothers of Stunting Toddlers in Puskesmas Anak Air Kota Padang - Yaumil Fauziah Milfa; Fitri Khairani; Annisa Namirah Nasution (Sumatera Medical Journal, 2025)
Background: Stunting is a developmental disorder in children caused by chronic malnutrition and recurrent infections. One effective way to convey information about nutrition to mothers of stunted toddlers is by watching videos. Objective: This study aimed to determine the changes in knowledge of mothers of stunted toddlers before and after watching intervention videos. Methods: A "One-group pretest and posttest" design was used in this study, conducted at the Anak Air Health Center in Padang City, from October 25, 2023, to January 15, 2024. A sample of 27 participants was selected using the Simple Random Sampling technique through the Random Number Application. Normality tests and bivariate analysis were performed using the Kolmogorov-Smirnov and Paired t-test (p < 0.05). Results: Statistical analysis using the paired t-test showed a significant change in knowledge scores before and after the video intervention, with a p-value of 0.001 (p < 0.05). This indicates that video media has a significant effect on the knowledge of mothers of stunted toddlers. Conclusion: The study concluded that there was an increase in knowledge among mothers of stunted toddlers before and after being exposed to video media intervention.